Outcomes of de novo belatacept‐based immunosuppression regimen and avoidance of calcineurin inhibitors in recipients of kidney allografts at higher risk for underutilization. Issue 11 (11th September 2022) - Patel, Ankita; Shertel, Tara; Wynd, Michael; Wadhera, Vikram; Serur, David; Schleich, Benjamin; Yushkov, Yuriy; Goldstein, Michael
Abstract: To describe an experience using a protocol using de novo belatacept (DNB) based maintenance immunosuppression in the setting of lymphocyte depletion. A retrospective, observational study was performed on 37 kidney transplant recipients treated with the DNB protocol, which was defined as belatacept initiated within 7 days after a kidney transplant with steroids and mycophenolate with anti‐thymocyte globulin (ATG) induction without concomitant calcineurin inhibitors (CNIs). Patients who received a deceased donor kidney meeting one or more of the following criteria: anticipated cold ischemia time (CIT) greater than 24 h, donation after cardiac death, donor acute kidney injury, and a Kidney Donor Profile Index (KDPI) >85% during the study period were included. Patient survival at 1 year was 97.3% and graft survival was 94.6%. Delayed graft function (DGF) occurred in 40.54% of the patients. Two patients experienced a Banff 1B acute cellular rejection. BK viremia was detected in 32.4% of patients. The mean estimated glomerular filtration rate (eGFR) calculated with the use of modification of diet in renal disease (MDRD) equation at 1 year in the study group was 54.7 ml/min/1.73 m 2 . We believe that utilization of the DNB protocol, which allows early CNI avoidance, may decrease organ discard rates. Summary at a Glance: Use of de novo Belatacept allowing avoidance of calcineurin inhibitors is a feasible and well tolerated option and has the potential to increase utilization of organs, reduce waitlist times for patients and reduce organ discard rate with good outcomes.